STRENGTH AND DURABILITY PROPERTIES OF E-WASTE PLASTICS IN CONCRETE - A REVIEW - Santhanam, Needhidasan; S., Mahaboob Basha (International Journal of Psychosocial Rehabilitation, 2020)
Rapid increase in the consumption of electronic equipment is determined all over the world in the twenty-first century, which has led to huge generation of e-waste. This evaluation paper seeks to have a look at the use of e-waste plastics in creation applications. This is an opportunity option to administer the generator quantity of the E-waste, and due to its coarse combination via some percentage of E plastic waste, it may be feasible to produce green concrete This analysis helps to promote safe and affordable green concrete production that integrates E-waste in the construction industry.